Phytochemical Investigation and Exploring the Citrullus Colocynthis Extracts as Antibacterial Agents Against Some Gram and Negative Bacteria Species - Hamad Hasan; Zuhir Akrim; Farag Shuib; Dala Abdraba (AlQalam Journal of Medical and Applied Sciences, 2025)
The Citrullus colocyn plant grows in some Libyan regions, especially at Al Gabal Al Akhder, and was considered as medicinal plant. In this study, the extracts of the seed and fruits of Citrullus colocyn. This plant was used as an antibacterial agent against gram-positive bacteria (Staphylococcus aureus, Bacillus cereus, and Streptococcus pneumonia) and gram-negative bacteria (Escherichia coli and Proteus vulgaris). Also, the phytochemical, total phenols, and antioxidant activities were detected. The results showed some natural product compounds such as carbohydrates and/or glycosides, flavonoids, sterols and/or triterpenes, cardiac glycoside, and small variations of their contents in aqueous and alcoholic extracts. For the antibacterial activities, higher concentrations of extracts (0.1 -0.8 g/100 ml) showed high effects compared with lower ones (0.0001 -0.1 g/100 ml) against the selected bacteria in this study. There is a relative increase in total phenols and antioxidant contents in fruit extracts compared with seeds. The study concluded that the presence of natural product compounds was the main reason for the inhibition of bacteria, and the difference of the effects was attributed to the effect of solvent polarizes during the extraction ينمو نبات الحنظل في العديد من المناطق الليبية وخاصة الجبل الاخضر ويتم تصنيفه من النباتات الطبية المهمه . في هذه الدراسة تم استخدام مستخلصات بذور وثمار الحنظل كمثبطات لأنواع مختلفة من البكتريا (موجبه جرام) مثل انواع بكتريا (Staphylococcus aureus , Bacillus cereus and Streptococcus pneumonia) وسالبه جرام مثل (Escherichia coli and Proteus vulgaris)). وتم اجراء التحليل الفيتوكيميائي و تقدير محتوى الفينولات الكلية ومضادات الاكسدة في كلا من البذور والثمار لنبات الحنظل. و قد بينت نتائج الدراسة وجود العديد من المركبات الكيميائية في المستخلصات مثل الكربوهيدرات او الجليكوسيدات والفلافونيدات والسيتروتيدات والتربينات زالجليكوسيدات القلبية وبنسب متفاوتة في المستخلصات ، كما بينت نتائج الدراسة ان التراكيز المرتفعة من المستخلصات والتي تراوحت ما بين ( 0.1 - 0.8 جرام / 100 مل ) كانت اكثر تثبيط من التراكيز الاقل من المستخلصات والتي تراوحت ما بين (0.0001 - 0.1 جرام / 100 مل)، وبينت النتائج ان الثمار احتوت على تراكيز اعلى من الفينولات الكلية ومضادات الاكسدة بالمقارنة مع محتوياتها في البذور. وخلصت الدراسة الي ان وجود مركبات النواتج الطبيعية في عينات نبات الحنظل قيد الدراسة قد تكون هي المسببة في التأثير لمستخلصاتها على انواع البكتريا قيد الدراسة.